American Caesar, Douglas MacArthur, 1880-1964 - Manchester, William (Little, Brown, 1978)
Part One Of Two PartsMacArthur was not only a lean, chiseled military genius and master of strategy; he also suffered unexplained lapses. For example, he knew of the Pearl Harbor attack but neglected to deploy his Philippine air force, a failure which resulted in its total destruction. And the success of his Inchon invasion was all but undone by the Chinese hordes that later swarmed across the Yalu--a response easily predicted, disastrously ignored."AMERICAN CAESAR is gracefully written, impeccably researched and scrupulous in every way...a thrilling and profoundly ponderable piece of work.